Numerical simulation of three-dimensional dynamic motion of a standard NACA model in an impact problem. (1st January 2012) - Nikseresht, Amir Hossein; Ghazizade-Ahsaee, Hossein
Impact problems associated with water entry have important applications in various aspects of naval architecture and ocean engineering. One of the most noticeable examples is bottom slamming of marine vehicles. In this research, a code which is based on the finite volume method is used to simulate the two phase flow water impact considering dynamic equations of motion with moving mesh. Volume of fluid (VOF) scheme is used to model the free surface shape. At first, water impact of a 3D wedge is numerically simulated. The results show a very good agreement with experimental data and show the accuracy and robustness of the solution. At last as an application, the 3D water impact of a standard NACA model which can be used as a flying boat keel is simulated.